OTHER COMPREHENSIVE INCOME IN THE INTERNATIONAL FINANCIAL REPORTING STANDARDS: A LITERATURE REVIEW - Nugraha, Oldiano Tito (Widya Mandala Surabaya Catholic University, 2024)
Research Purposes. This research aims to examine studies regarding investor and contractual profits from Other Comprehensive Income (OCI), as well as its components can provide more evidence regarding whether there are characteristics that differentiate between OCI.Research Methods. This research is research using literature review.The process of reviewing selected articles focuses on understanding the problem, context, complexity and subjectivity of researchers in studying and interpreting OCI’s conceptions and OCI components (and AOCI) and their various relevance that are beneficial to investors in IFRS. Google search, www.semanticcholar.org and onlinelibrary.wiley.com were used to find journal special issues.Research Results and Findings. OCI information and OCI components in the IFRS standard income statement are little use to investors, especially for assessing risk in making investment decisions. Investors should be careful not to overly consider OCI information and OCI components (and AOCI) when making investment decision, including debt contracts.